Improvement in documentation of intake and output chart - Ling .W.W (Universiti Kebangsaan Malaysia, 2011)
Intake and Output (I/O) records in hospitals were often found to be incomplete and illegible. The form used to record I/O is not user-friendly — i.e., they feature miniscule boxes, ‘total’ lines that do not correspond with shift changes and lack of instructions. Complaints often received from Specialists & Doctors regarding calculation errors or no totalling of I/O. Moreover, Nursing Sisters objective rounds often saw incompleteness of I/O chart. This study aims to identify the types of mistakes in recording the existing I/O chart. The second aim is to find out whether shift totalling of I/O chart helps in reducing mistakes. We try to determine whether the identified mistakes were repeated in the new I/O Chart. This study was conducted from October till December 2010 in 9 selected wards in Sibu Hospital. Data collection was divided into 3 phases. A pre-implementation audit using a checklist was carried out. The compliance rate of completeness of documentation of I/O Chart was 63%. A one month trial of new I/O chart was being done in the selected 9 wards. Post implementation audit showed a significant improvement of compliance rate (88%). Feedback from health care workers (N=110) showed that, 89% of doctors (n=17) and 60% of nurses (n=93) in the sample prefer to use the new format as more practical and relevant to the changing shift of nurses and doctors’ ward round. It is suggested to implement the new format to increase compliance rate of documentation of I/O charting. Briefing should be given to nurses periodically and the new format should be introduced to nursing students in nursing colleges.